Endovascular Alternatives to Transhepatic Shunt Creation - Sinha, Ishan; Goldman, Daryl T.; Patel, Rahul S.; Nowakowski, Francis S. (Seminars in Interventional Radiology, 2023)
Portomesenteric decompression is often necessary to treat patients with refractory symptoms of portal hypertension. When transjugular or direct intrahepatic portosystemic shunt creation is not feasible or is inadequate, surgical portosystemic shunt creation is considered, which carries significant morbidity and mortality in these high-risk patients. Surgery is further complicated in patients with portomesenteric thrombosis who require concurrent thrombectomy and long-term anticoagulation. In this article, we outline the technique for performing advanced endovascular alternatives to intrahepatic portosystemic shunt creation including mesocaval and splenorenal shunting. We will also discuss some of the clinical considerations for treating these patients with symptomatic portal hypertension and portomesenteric thrombosis.
Keywords: mesocaval shunt; splenorenal shunt; portal vein thrombosis; interventional radiology; transjugular intrahepatic portosystemic shunt